Membentuk Pribadi yang Tangguh: Pentingnya Guru Pendidikan Agama Kristen Menanamkan Sikap Disiplin pada Anak Hiperaktif - Elieser Marampa; Haraitoni D. Sianturi; Korina Sanosa; Gibson Sibarani; Erny Dethan (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
This study aims to determine and analyze the role of Christian religious education teachers in instilling discipline in hyperactive children. In obtaining data, the author uses a descriptive qualitative approach with a literature study method. Data collection techniques are carried out through studies of reference books, journal articles, and website as reference references. The results of this study indicate that Christian religious education teachers not only contribute to the level of completing children's cognitive abilities but also holistically need to pay attention to children's overall development in terms of cognitive, affective, psychomotor and children's spirituality. Instilling discipline in hyperactive children is one way of dealing with hyperactive behavior in children so that children can be controlled and directed appropriately. The role of Christian religious education teachers in instilling discipline in hyperactive children includes: 1) Building self-control, 2) Teaching children gently, 3) Giving educational sanctions, 4) Carrying out continuous guidance. Thus, in the future, children will have better personalities and be able to interact with children in general.